Life cycle assessment of energy consumption and GHG emission for sewage sludge treatment and disposal: a review - Yu, Shilin; Deng, Shuanghui; Zhou, Ao; Wang, Xuebin; Tan, Houzhang (Frontiers in Energy Research, 2023)
With increasing urbanization and population growth, the generation of municipal sewage sludge is huge and rapidly increasing. To minimize resource inputs and pollution emissions during sludge disposal, it is crucial to conduct enviroment impact analysis and sustainability assessment of different stategied based on life cycle assessment (LCA). The aim of this review is to compare the energy consuption and GHG emission of existing sludge management options for energy and nutrient recovery. Simultaneously, the characteristic of sewage sludge and the potential for sludge conversion from waste to valuable products are assessed. It is worth emphasizing that, as part of organic solid waste, the reduction and harmless disposal of sludge is the primary goal, and on this basis, the resource utilization should be considered. Although its high mositure content and ash content make sludge unsuitable as fuel, and the potential risk of heavy metal contamination makes it less applicable as organic fertilizer, energy and material recovery during disposal process can reduce disposal costs and environmental impact. In the context of the current limitations reviewed, the level of potential GHG emissions of existing sludge treatment and disposal routes is: composting > anaerobic digestion > pyrolysis > incineration. In suitable sludge treatment routes there is piotential to achieve negative GHG emissions. by replacing fossil fuels for heat and electricity generation or as fertilizer substitute The development and application of future sludge management stategies should aim at reduction and harmless disposal, reducing the costs of operating and environmental burden by means of resourceization.